Clinical implications of low skeletal muscle mass in early-stage breast and colorectal cancer. Issue 4 (4th June 2018) - Cespedes Feliciano, Elizabeth; Chen, Wendy Y.
Abstract : Although obesity has now been widely accepted to be an important risk factor for cancer survival, the associations between BMI and cancer mortality have not been consistently linear. Although morbid obesity has clearly been associated with worse survival, some studies have suggested a U-shaped association with no adverse association with overweight or lower levels of obesity. This 'obesity paradox' may be due to the fact that BMI likely incompletely captures key measures of body composition, including distribution of skeletal muscle and adipose tissue. Fat and lean body mass can be measured using clinically acquired computed tomography scans. Many of the earlier studies focused on patients with metastatic cancer. However, skeletal muscle loss in the metastatic setting may reflect end-stage disease processes. Therefore, this article focuses on the clinical implication of low skeletal muscle mass in early-stage non-metastatic breast and colorectal cancer where measures of body composition have been shown to be strong predictors of disease-free survival and overall survival and also chemotherapy toxicity and operative risk.